Model Pembelajaran Kooperatif dalam Pembelajaran Matematika Ditinjau dari Perspektif Filsafat Pendidikan (Aksiologi) - Sugiarti, Lana; Rukiyati (Jurnal PEKA (Pendidikan Matematika), 2026)
By examining mathematics education through the lens of educational philosophy, this article will analyze several learning models, focusing on cooperative learning methods. From an axiological perspective, this study raises the question of how cooperative learning models are understood. The rationale for their development, importance, and strategies for implementing cooperative learning models are all discussed in this axiological research. This article uses a qualitative literature review as its data source; this review specifically addresses cooperative learning approaches as they relate to mathematics education. In this study, we conclude that one of the goals of implementing cooperative learning models in schools is to help students and teachers work together to achieve learning goals. Among the many suggested approaches to mathematics teaching, cooperative learning models stand out. Because students are closely observed and actively engaged in learning activities in cooperative learning models, teachers and students can have more meaningful interactions. Encouraging students to work together in mathematics class is a surefire way to improve their abilities, understanding, and final grades. Students' qualities and needs should be considered when selecting cooperative learning strategies.